Listening to women’s voices: the experience of giving birth with paramedic care in Queensland, Australia - Belinda Flanagan; Bill Lord; Rachel Reed; Gail Crimmins (BMC Pregnancy and Childbirth, 2019)
Abstract Background Unplanned out-of-hospital birth is generally assumed to occur for women who are multiparous, have a history of a short pushing phase of labour or are experiencing a precipitate birth. However, there is little research that examines the woman’s perspective regarding factors that influenced their decision on when to access care. This research aimed to explore women’s experience of unplanned out-of-hospital birth in paramedic care. Due to the size of the data in the larger study of ‘Women’s experience of unplanned out-of-hospital birth in paramedic care’ [1], this paper will deal directly with the women’s narrative concerning her decision to access care and how previous birth experience and interactions with other healthcare professionals influenced her experience. Method Narrative inquiry, underpinned from a feminist perspective, was used to guide the research. Twenty-two women who had experienced an unplanned out-of-hospital birth within the last 5 years in Queensland, Australia engaged in this research. Results The decision of a woman in labour to attend hospital to birth her baby is influenced by information received from healthcare providers, fear of unnecessary medical intervention in birth, and previous birth experience. All themes and subthemes that emerged in the women’s narratives relate to the notion of birth knowledge. These specifically include perceptions of what constitutes authoritative knowledge, who possesses the authoritative knowledge on which actions are based, and when and how women use their own embodied knowledge to assess the validity of healthcare workers’ advice and the necessity for clinical intervention. Conclusions The women interviewed communicated a tension between women’s knowledge, beliefs and experience of the birth process, and the professional models of care traditionally associated with the hospital environment. It is essential that information provided to women antenatally is comprehensive and comprehensible. The decisions women make concerning their birth plan represent the women’s expectations for their birth and this should be used as a means to openly communicate issues that may impact the birth experience.